Pathways to metallic hydrogen - Silvera, Isaac F.; Deemyad, Shanti (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The traditional pathway that researchers have used in the goal of producing atomic metallic hydrogen is to compress samples with megabar pressures at low temperature. A number of phases have been observed in solid hydrogen and its isotopes, but all are in the insulating phase. The results of experiment and theory for this pathway are reviewed. In recent years a new pathway has become the focus of this challenge of producing metallic hydrogen, namely a path along the melting line. It has been predicted that the hydrogen melt line will have a peak and with increasing pressure the melt line may descend to zero Kelvin so that high pressure metallic hydrogen may be a quantum liquid. Even at lower pressures hydrogen may melt from a molecular solid to an atomic liquid. Earlier attempts to observe the peak in the melting line were thwarted by diffusion of hydrogen into the pressure cell components and other problems. In the second part of this paper we present a detailed description of our recent successful demonstration of a peak in the melting line of hydrogen.